ANALISIS PENYIDIKAN TINDAK PIDANA PERSETUBUHAN TERHADAP ANAK - MARUDIN, EKO (Dinamika Hukum, 2016)
The purpose of this study was to determine and analyze the process of law enforcement against criminal acts of intercourse against a child under Law - Child Protection Act and the Criminal Code (Criminal Code) which occurred in the jurisdiction of Police Wonogiri. It also wants to identify and analyze the barriers that are found in the implementation of the process of law enforcement in such cases. Background to the dispute that the investigation of criminal offenses against children sexual intercourse is one of a series of processes legal action taken by the police investigators. The probe is intended to verify a report or regarding the report or inspection information - information relating to criminal offenses against children sexual intercourse. Investigator Police as an institution has a duty and responsibility to do the law enforcement process in its implementation still find obstacles in its implementation. This study by type, including the type of sociological and juridical research by its nature is a descriptive study. The data used are primary data and secondary data collection techniques with interviews and study the literature by using qualitative analysis techniques. It can be concluded that the process of criminal enforcement against criminal acts of intercourse against children committed by police investigators from Wonogiri been implemented as Child Protection Law and the Code of Criminal Procedure, as stipulated in Article 7 of the Criminal Procedure Code. Barriers - barriers that are found in the process of investigation of the criminal act of intercourse against children include: not follow her principles enactment of legislation, lack of clarity about the meaning of the word in the legislation that resulted in the existence of multiple interpretations, limited human resource capacity investigators, yet inadequate infrastructure as well as culture and public understanding of the laws - laws. Keywords: Analysis of Investigation, Crime Intercourse, Kids